Evidence of clinical efficacy and pharmacological mechanism of N-butylphthalide in the treatment of delayed encephalopathy after acute carbon monoxide poisoning - Song, Huiping; Yue, Aochun; Zhou, Xudong; Han, Wei; Li, Qin (Frontiers in Neurology, 2023)
Objective Based on network meta-analysis (NMA) and network pharmacology approaches, we explored the clinical efficacy of different regimens, and clarified the pharmacological mechanisms of N-butylphthalide (NBP) in the treatment of delayed encephalopathy after acute carbon monoxide poisoning (DEACMP). Methods Firstly, NMA was conducted to obtain the ranking of the efficacy of different regimens for the treatment of DEACMP. Secondly, the drug with a relatively high efficacy ranking was selected and its mechanism of treatment for DEACMP was identified through a network pharmacology analysis. By the use of protein interaction and enrichment analysis, the pharmacological mechanism was predicted, and molecular docking was subsequently carried out to verify the reliability of the results. Results A total of 17 eligible randomized controlled trials (RCTs) involving 1293 patients and 16 interventions were eventually included in our analysis from NMA. Mesenchymal stem cells (MSCs) + NBP significantly increased mini-mental state examination (MMSE) and Barthel index (BI) scores; NBP + dexamethasone (DXM) was the most effective treatment in improving the activity of daily living (ADL) scores; NBP significantly decreased national institutes of health stroke scale (NIHSS) scores; Xingzhi-Yinao granules (XZYN) had more advantages in improving Montreal cognitive assessment (MoCA) scores, translational direct current stimulation (tDCS) had a significant effect in improving P300 latency and P300 amplitude and Kinnado + Citicoline had the most obvious effect in improving malondialdehyde (MDA). Meanwhile, by network pharmacology analysis, 33 interaction genes between NBP and DEACMP were obtained, and 4 of them were identified as possible key targets in the process of MCODE analysis. 516 Gene ontology (GO) entries and 116 Kyoto Encyclopedia of Gene and Genome (KEGG) entries were achieved by enrichment analysis. Molecular docking showed that NBP had good docking activity with the key targets. Conclusion The NMA screened for regimens with better efficacy for each outcome indicator in order to provide a reference for clinical treatment. NBP can stably bind ALB, ESR1, EGFR, HSP90AA1, and other targets, and may play a role in neuroprotection for patients with DEACMP by modulating Lipid and atherosclerosis, IL-17 signaling pathway, MAPK signaling pathway, FoxO signaling pathway, PI3K/AKT signaling pathway.